Examination of lower-upper limb of power and force parameters of elite athletes - Samet Aktaş; Oktay Çakmakçı (Physical Education of Students, 2020)
Background and Study Aim. In this study, it is aimed to evaluate the power and force parameters of lower and upper extremities of the individual and team athletes who practice different branches.